Single organelle analysis to characterize mitochondrial function and crosstalk during viral infection - Schneider, Annika (Sci Rep, 2019)
Mitochondria are key for cellular metabolism and signalling processes during viral infection. We report a methodology to analyse mitochondrial properties at the single-organelle level during viral infection using a recombinant adenovirus coding for a mitochondrial tracer protein for tagging and detection by multispectral flow cytometry. Resolution at the level of tagged individual mitochondria revealed changes in mitochondrial size, membrane potential and displayed a fragile phenotype during viral infection of cells. Thus, single-organelle and multi-parameter resolution allows to explore altered energy metabolism and antiviral defence by tagged mitochondria selectively in virus-infected cells and will be instrumental to identify viral immune escape and to develop and monitor novel mitochondrial-targeted therapies.